Surface Texturing with Hemispherical Cavities to Improve Efficiency in Silicon Solar Cells - D. W. de Lima Monteiro; F. P. Honorato; R. F. de Oliveira Costa; L. P. Salles (International Journal of Photoenergy)
Improvement of solar-cell efficiency at a minimum possible cost addition is constantly sought, and this is often achieved at incremental percentage steps. Among a number of alternatives, antireflective coatings and surface texturing are the most prominent. This paper presents an alternative texturing method of crystalline silicon in an attempt to improve the efficiency of photon transmission through the surface and collection in the bulk. The method relies on anisotropic etching of bulk silicon and requires only a single oxide mask and two etching steps with a KOH or TMAH aqueous solution. The surface texture consists of smooth hemispherical cavities, which do not demand a lithographic mask or intricate technology processes to obtain the hemispherical cavities. This method can be applied to increase the profile area of the originally flat frontal surface exposed to light and consequently increase the effective width of the depletion region. The latter implies a higher probability of photon collection, contributing to the improvement of the conversion efficiency of the device. The textured nontilted silicon solar-cell transmittance under small solar incidence angles at dawn and sunset is improved compared to a flat surface, increasing the photocurrent.